THEORY INTO PRACTICE: UNIVERSITY STUDENTS' COGNITION OF THE USE LOGARITHM IN EXPRESSING THE MAGNITUDE OF EARTHQUAKES - Canca, D.; Altun, S. (IATED-INT ASSOC TECHNOLOGY EDUCATION & DEVELOPMENT, 2010)
The aim of the study is determining the level of transfer of a theoretical subject in mathematics into practice as a general knowledge. In this context, university students' knowledge on the basics of the subject logarithm and its use in earthquakes is investigated. The study group consists of 255 undergraduate students from Yildiz Technical University who attend summer program in the Departments of Mathematics and Physics. Students are asked questions on the effects of earthqukes (an important concept for Turkey, which has resulted in thousands of deaths in Istanbul and the rest of the country) according to the Richter scale where logarithm (which is one of the general subjects both in high school and university programs) is used. Furthermore, same study is also applied to a similar group by introducing clues which show ways to use logarithm in the solution of the problem. At the end, students were also interviewed about the whole process. Results introduce that although students know how to solve logarithm problems, they were unaware of the use of it in seismology, which is widely expressed by the Richter scale in daily life. In addition, it is revealed that clues that refer prior knowledge do assist students in trying to find a right answer for a question, but remain unsatisfactory where related practices are not mentioned in the courses.
Keywords: Theory into practice; prior knowledge; mathematics; daily life; clues; Education & Educational Research